Efficacy of indigo naturalis nanofibrous patches in the treatment of chronic plaque psoriasis: a 4-week prospective, randomized, semi-compartmental paired, positive drug-controlled trial - Yuechun Zhao; Jiaqi Li; Ningxin Zhang; Mingyue Liu; Pengyu Wang; Ning Li; Ruodan Xu; Ping Song (Frontiers in Pharmacology)
BackgroundIndigo Naturalis (IN) has been traditionally used for psoriasis treatment. We developed an IN-poly (ε -caprolactone, PCL)/poly (ethylene oxide, PEO) nanofibrous patch using electrospinning technology. Preliminary studies demonstrated its potential to reduces keratinocyte proliferation, inflammation, and neovascularization, addressing limitations of conventional IN formulations such as poor absorption and skin staining.AimsTo evaluate the safety and efficacy of the IN-PCL/PEO patch for chronic plaque psoriasis.MethodsThe clinical trial included 36 patients diagnosed with chronic plaque psoriasis. Two symmetrical psoriatic lesions from each eligible patient were selected by dermatologists and randomly assigned to receive either calcipotriol ointment (control group) or IN-PCL/PEO nanofibrous patch (test group) for 4 weeks. Primary outcomes included Psoriasis Area and Severity Index (PASI), while secondary outcomes assessed Patient Global Assessment (PGA), skin irritation, and patient satisfaction. Safety was monitored via blood, urine, and liver/kidney function tests.Results30 subjects completed the treatment trial with both IN and CA. In the test group (n = 30), PASI scores decreased from 6.30 ± 2.23 to 2.13 ± 1.57 (p < 0.001). Within this group, 90.0% (27/30) achieved PASI 50% and 43.3% (13/30) achieved PASI 75. No skin irritation cases were reported (0.0%). While PASI scores decreased from 6.23 ± 2.27 to 2.23 ± 1.50 (p < 0.001) in the control group, 86.7% (26/30) achieved PASI 50% and 33.3% (10/30) achieved PASI 75, with 6.7% (2/30) experiencing irritation. All safety parameters remained within standard reference ranges.ConclusionThe IN-PCL/PEO patch demonstrated efficacy comparable to calcipotriol ointment, with improved safety and tolerability, suggesting its potential as an alternative psoriasis treatment.